Comparative evaluation of APRI and MELD scores in the prediction of complications of chronic hepatitis in patients infected with hepatitis B or C viruses in Lubumbashi, democratic republic of Congo - Arsène Kabamba-Tshikongo; Adolphe Baleebenga; Bernard Kalunga-Tompa; Claude Mwamba-Mulumba; Henry Manya-Mboni; Cedrick Mutombo-Shakalenga; Pierrot Mwamba-Tshilumba; Sébastien Bontems; Géraldine Dessilly; Benoît Kabamba-Mukadi; Albert Longanga-Otshudi (Journal of Clinical Virology Plus)
The indication for treatment of viral hepatitis B and C depends on the degree of deterioration of liver function and secondarily viral load. APRI and MELD scores are WHO-validated tests for the assessment of liver fibrosis. They are inexpensive and non-invasive. Many patients suffer from viral hepatitis B or C in the Democratic Republic of Congo. These scores are an asset in the medical management of these patients. The objective of this study was to compare APRI and MELD scores in the prediction of fibrosis in patients with chronic viral hepatitis B in Lubumbashi. It included infected patients followed in the gastroenterology departments of the hospitals of Lubumbashi and the Center of Excellence and Expertise for Viral Hepatitis and other Pathologies (CEEHP). Biological parameters of patient samples were evaluated to calculate APRI and MELD scores. Analytical performance of APRI and MELD scores was evaluated by using liver biopsy as gold standard.The APRI and MELD scores had a sensitivity of 100 % and a specificity of 93.5 and 88.6 %, respectively. In the fibrosis group of patients infected with HBV, the mean APRI score was of 1.89 whereas the mean MELD score was of 12.4 Incorporating these scores in routine clinical practice could reduce the morbidity rate, the costs related to the practice of liver biopsy and thus improve the routine management of viral hepatitis in Lubumbashi.